Clinical and neuroimaging findings in 33 patients with MCAP syndrome: A survey to evaluate relevant endpoints for future clinical trials. Issue 5 (20th January 2021) - Garde, Aurore; Guibaud, Laurent; Goldenberg, Alice; Petit, Florence; Dard, Rodolphe; Roume, Joelle; Mazereeuw‐Hautier, Juliette; Chassaing, Nicolas; Lacombe, Didier; Morice‐Picard, Fanny; Toutain, Annick; Arpin, Stéphanie; et al.
Abstract: Megalencephaly‐CApillary malformation‐Polymicrogyria (MCAP) syndrome results from somatic mosaic gain‐of‐function variants in PIK3CA . Main features are macrocephaly, somatic overgrowth, cutaneous vascular malformations, connective tissue dysplasia, neurodevelopmental delay, and brain anomalies. The objectives of this study were to describe the clinical and radiological features of MCAP, to suggest relevant clinical endpoints applicable in future trials of targeted drug therapy. Based on a French collaboration, we collected clinical features of 33 patients (21 females, 12 males, median age of 9.9 years) with MCAP carrying mosaic PIK3CA pathogenic variants. MRI images were reviewed for 21 patients. The main clinical features reported were macrocephaly at birth (20/31), postnatal macrocephaly (31/32), body/facial asymmetry (21/33), cutaneous capillary malformations (naevus flammeus 28/33, cutis marmorata 17/33). Intellectual disability was present in 15 patients. Among the MRI images reviewed, the neuroimaging findings were megalencephaly (20/21), thickening of corpus callosum (16/21), Chiari malformation (12/21), ventriculomegaly/hydrocephaly (10/21), cerebral asymmetry (6/21) and polymicrogyria (2/21). This study confirms the main known clinical features that defines MCAP syndrome. Taking into account the phenotypic heterogeneity in MCAP patients, in the context of emerging clinical trials, we suggest that patients should be evaluated based on the main neurocognitive expression on each patient. Abstract :